2016
DOI: 10.1002/ejp.851
|View full text |Cite
|
Sign up to set email alerts
|

Experimental pain induces attentional bias that is modified by enhanced motivation: An eye tracking study

Abstract: This study was the first that revealed the impact of acute experimental pain on attentional bias towards pain-related information in healthy individuals through eye tracking. It may provide a possible solution to reduce hypervigilance towards pain-related information by altering the motivational relevance. WHAT DOES THIS STUDY ADD?: (1) This study revealed the impact of experimental pain on attentional bias in healthy individuals; (2) This study may provide a possible approach of altering motivational relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
2
19
0
1
Order By: Relevance
“…As such, the present pattern of results is unsurprising. The results are also in line with the majority of studies to date that, using diverse cognitive paradigms, have explored attentional biases towards pain‐related information in healthy individuals recruited specifically as the target population (Priebe et al, ; Sun et al, ; Vervoort et al, ) or when recruited as a comparison group for chronic pain patients (Fashler & Katz, ; Schoth, Godwin et al, ). Furthermore, by combining a reliable method such as eye tracking (Skinner et al, ) in conjunction with real‐world images that reflect processes normally occurring in people's everyday lives (e.g., seeing someone in pain or viewing pain‐related scenes in the news media), the present study offers a good balance between the internal validity and experimental control needed for scientific progress and the ecological validity necessary for generalizing experimental results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As such, the present pattern of results is unsurprising. The results are also in line with the majority of studies to date that, using diverse cognitive paradigms, have explored attentional biases towards pain‐related information in healthy individuals recruited specifically as the target population (Priebe et al, ; Sun et al, ; Vervoort et al, ) or when recruited as a comparison group for chronic pain patients (Fashler & Katz, ; Schoth, Godwin et al, ). Furthermore, by combining a reliable method such as eye tracking (Skinner et al, ) in conjunction with real‐world images that reflect processes normally occurring in people's everyday lives (e.g., seeing someone in pain or viewing pain‐related scenes in the news media), the present study offers a good balance between the internal validity and experimental control needed for scientific progress and the ecological validity necessary for generalizing experimental results.…”
Section: Discussionsupporting
confidence: 85%
“…Two used a free‐viewing task with face pairs, one reporting bias towards pain expressions relative to neutral faces (initial fixation location and absolute gaze duration up to 1,000 ms) (Priebe, Messingschlager, & Lautenbacher, ), and the other an initial orienting bias (time to first fixation) towards pain expressions relative to neutral faces in low pain catastrophizers (Vervoort, Trost, Prkachin, & Mueller, ). Another using the visual‐probe task found participants who completed a preceding experimental pain task showed increased bias (first‐run dwell time) for pain‐related images compared to participants not exposed to the task (Sun, Wang, & Luo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, 2012Yang et al, , 2013Vervoort et al, 2013;Sun et al, 2016;Todd et al, 2016a,b). From the data, we took a number of measures that are associated with initial orienting of attention.…”
Section: Eye-tracking Measuresmentioning
confidence: 99%
“…Fixations were defined as a period of at least 100 ms in which the participant held their gaze within an area of 0.5°radius consistent with recent eye-tracking studies (e.g. Yang et al, 2012Yang et al, , 2013Vervoort et al, 2013;Sun et al, 2016;Todd et al, 2016a,b). In addition, we assessed the percentage of trials on which the first fixation was on the pain-related stimulus (e.g.…”
Section: Eye-tracking Measuresmentioning
confidence: 99%
“…Third, according to physical and social pain overlap theory ( Eisenberger, 2012 ), pain indicated by social cue would be the same as indicated by physical cue, thus further research could consider investigating the influence of social cue to children’s empathy for pain. Sun et al (2016) use pictorial visual-probe task to test whether verbal instruction would influence adults’ attentional bias to painful picture, and they found that the experimental group which received verbal instruction before the tasks would exhibit weaker attention bias toward painful pictures. Fourth, more types of cues could be used, and a study indeed has found that uncertain cues would induce stronger reaction to pain than certain cues ( Lin et al, 2014 ).…”
Section: Strengths Limitation and Conclusionmentioning
confidence: 99%